Development Of Teacher's Professional Competency In Realizing Quality Of Human Resources In The Basic School - Nurul Annisa; A Akrim; Asrar Aspia Manurung (Indonesian Journal of Education and Mathematical Science, 2020)
Teacher competence in carrying out the teaching and learning process is not only determined by their competence, but also the competence of all those involved in managing all available resources. This research focuses on the professional competence of teachers in the teaching and learning process that emphasizes the achievement of teachers in carrying out these activities. Nowadays, teacher performance shows that in conducting the teaching and learning process begins with making a learning plan and ends with implementing it to students, and also the achievement of the teacher in conducting the teaching and learning process is how the teacher in creating a fun teaching and learning situation and a pleasant school environment conducive. For this reason, teachers must optimize their tasks in developing their abilities, in the form of professional competence. Keywords:Teacher Competence; Personality Competence; Resources;Quality